Algebraic Curves and Finite Fields 2014
DOI: 10.1515/9783110317916.23
|View full text |Cite
|
Sign up to set email alerts
|

Good towers of function fields

Abstract: SummaryAlgebraic curves are used in many different areas, including error-correcting codes. In such applications, it is important that the algebraic curve C meets some requirements. The curve must be defined over a finite field F q with q elements, and then the curve also should have many points over this field. There are limits on how many points N (C) an algebraic curve C defined over a finite field can have.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 39 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…Moreover, from [6, V.4,VII.5] we see that if δ is odd and all prime ideals p i occurring in the decomposition of n have even degree, among all the points of x 0 (n) that are lying above a given elliptic point of x(1) there are exactly 2 s that are ramified in the covering x(n)/x 0 (n) (with ramification index q + 1). The latter statement is equivalent to saying that these 2 s points of x 0 (n) have ramification index 1 in x 0 (n)/x (1). Counting the number of points of x 0 (n) lying above the supersingular points of x(1) now is direct and yields the stated lower bound on N 1 (x 0 (n)).…”
Section: Rational Points On Reductions Of Drinfeld Modular Curvesmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, from [6, V.4,VII.5] we see that if δ is odd and all prime ideals p i occurring in the decomposition of n have even degree, among all the points of x 0 (n) that are lying above a given elliptic point of x(1) there are exactly 2 s that are ramified in the covering x(n)/x 0 (n) (with ramification index q + 1). The latter statement is equivalent to saying that these 2 s points of x 0 (n) have ramification index 1 in x 0 (n)/x (1). Counting the number of points of x 0 (n) lying above the supersingular points of x(1) now is direct and yields the stated lower bound on N 1 (x 0 (n)).…”
Section: Rational Points On Reductions Of Drinfeld Modular Curvesmentioning
confidence: 96%
“…By computing the precise formula for the genus and the number of rational points on reductions of F q [T ]-Drinfeld modular curves X 0 (n), Gekeler [8] showed that for a series (n k ) k∈N of polynomials of A coprime with an irreducible polynomial P ∈ A, and whose degrees tend to infinity, the family of Drinfeld modular curves X 0 (n k )/F P attains the Drinfeld-Vladut bound when considered over F (2) P . In case n k = T k and P = T − 1, explicit equations for the modular curves X 0 (T k ) were given in [2], while some more general examples (including defining equations in generic A-characteristic 0) were given in [1]. For A = F q [T ] and δ = 1 the situation has therefore to a large extent been investigated both theoretically and explicitly.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations